Essays on Stereotype Threat and Consumer Responses - Dallabrida, Yuri Marcel (2023)
This research aims to comprehend whether stereotype threat induces changes in consumer responses and, if so, for whom it is observed. Stereotype threat theory states that reminding individuals of negative stereotypes about a group they belong to leads them to behave in a manner that confirms the stereotype. The theory was developed mostly focusing on academic and cognitive performance, and a series of meta-analyses support it. However, evidence on non-performance-related outcomes was only systematically evaluated in the educational context. Moreover, there is little research investigating the theory in the marketing context. I explore this in two papers. First, I present a systematic review and meta-analysis on the effect of stereotype threat on variables other than performance. This is the first meta-analysis not focused on performance that extends beyond only research related to education. The results indicate that stereotype threat leads to responses that reinforce the stereotypes; thus, extending what had been previously revealed for performance. Furthermore, the meta-analysis also revealed important moderators of stereotype threat’s effect: the negatively stereotyped group – the effect was only significant for women and Blacks – and type of measure – the effect was significantly larger for variables accessed with behavioral measures. Second, I describe four experiments on the effects of stereotype threat on consumer responses. The results show that stereotype threat only affected actual behavior (product preference) and that this effect was mediated by an increased use of heuristics. Moreover, the experiments also reveal a relevant generational difference in how individuals respond to stereotype threat. Lastly, I present a general discussion, summarizing the main contributions, implications, and future directions for research on stereotype threat from a marketing perspective.